(untitled) - Johnson, Thomas (Boston, 1987)
Now in its ninth printing, Relevance Lost has had a profound impact onthe way management accounting systems operate in the 1990s. Featuring a new preface, this edition explores the evolution of management accounting, and stresses the importance of rapid technological change in today's global and domestic competition. "...(this book) could be a survival manual for troubled industries."--The Wall Street Journal.
Keywords: Managerial accounting,Managerial accounting; History,History; United states